Transition Scenarios. From Unipolar to Multipolar World Geopolitics - Guendel Angulo, Hermann (2024)
Geopolitical changes are taking place at a time when the old power players who, under bipolar-unipolar geopolitical relations, hegemonized the capitalist world system are now confronted, and even displaced, by emerging actors, bringing the possibility of a new world order. Given this, the expectation arises of an opening to different forms of economic exchange and international interaction. This paper analyzes the current process in world scenarios and its implications, seeking to justify the expectation of significant change caused by this era.